2013
DOI: 10.1264/jsme2.me12177
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Quantification of <i>Phytophthora nicotianae</i> and <i>P. cactorum</i>, and Distribution Analyses in Strawberry Greenhouses by Duplex Real-time PCR

Abstract: Phytophthora nicotianae and P. cactorum cause Phytophthora rot of strawberry. A duplex real-time PCR technique for simultaneous detection and quantification of the two pathogens was developed. Species-specific primers for P. nicotianae and P. cactorum were designed based on the internal transcribed spacer regions (ITS) of rDNA and the ras-related protein gene Ypt1, respectively. TaqMan probes were labeled with FAM for P. nicotianae and HEX for P. cactorum. Specificities were demonstrated using 52 isolates, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…The Ypt 1 gene target region was used as a molecular marker to identify P. fragariae (Ioos et al ., ) and to develop a multiplex real‐time PCR detection method for P. ramorum, P. kernoviae, P. citricola and P. quercina (Schena & Cooke, ; Li et al ., ). Recently, the same gene was used for real‐time detection of P. cactorum in strawberry (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The Ypt 1 gene target region was used as a molecular marker to identify P. fragariae (Ioos et al ., ) and to develop a multiplex real‐time PCR detection method for P. ramorum, P. kernoviae, P. citricola and P. quercina (Schena & Cooke, ; Li et al ., ). Recently, the same gene was used for real‐time detection of P. cactorum in strawberry (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The primers designed for the ITS region and the YPT1 gene were utilized with sufficient results. The assay was able to detect 10 fg and 1 pg of targeted DNA from P. nicotianae and P. cactorum , respectively [112]. The triple approach of detecting Malus Miller pathogens using qPCR was also verified in a recent study.…”
Section: Detection Methods Of Plant Pathogenic Fungal Speciesmentioning
confidence: 99%
“…The Kageyama + Mag method was found to be an effective extraction method for soil samples (Li et al 2011(Li et al , 2013Ishiguro et al 2013) due to the high extraction efficiency and strong purification capability. In our tests, it was also shown that, for some soil types, such as Letters in Applied Microbiology 61, 179--185 © 2015 The Society for Applied Microbiology gley soil, brown forest soil and grey lowland soil, the Kageyama + Mag method performed more efficiently than the Extrap Soil DNA kit, with higher DNA yields.…”
Section: Selection Of Soil Dna Extraction Methodsmentioning
confidence: 99%
“…Accurate detection, diagnosis and species identification is fundamental to disease management. The molecular quantification of Phytophthora and Pythium species in complex soil environments originally relied on methods involving DNA/DNA hybridization (Schena et al 2004;Schena and Cooke 2006;Li et al 2010Li et al , 2013Li et al , 2014Schroeder et al 2013). However, no previous studies have included the determination of DNA extraction efficiency for accurate quantification of soil-borne pathogenic oomycetes.…”
Section: Introductionmentioning
confidence: 99%